Flash calculations with specified entropy and stagnation enthalpy - Castier, Marcelo; Kanes, Rym; Véchot, Luc N. (Fluid phase equilibria, 2016)
Finding the properties of a stream leaking from a pressure vessel, assuming it is in thermodynamic equilibrium, requires the solution of a phase equilibrium problem with known values of component amounts, entropy, and stagnation enthalpy. If part of dynamic simulations of leaking vessels, these calculations need to be executed hundreds or thousands of times. Ideally, they should be fast and never fail, even when executed for difficult conditions, such as high pressure systems close to phase boundaries or to critical points. This paper proposes a single loop algorithm to solve flash problems with specified values of entropy and stagnation enthalpy. The results show that it is much faster than a nested loop algorithm for the same purpose, but occasionally fails to converge especially very close to phase boundaries. The nested loop algorithm succeeded in these situations however at large computational cost because of multiple phase additions and removals during the course of the iterations. A satisfactory balance of speed and reliability was obtained by favoring the single loop algorithm but, when it fails, using the nested loop algorithm as a backup procedure.